Protective effect of Allium hookeri water extract and its main compound, Cycloalliin, on foam cell formation in THP-1-derived macrophages - Ha-Rin Moon; Jung-Mi Yun (Food & Nutrition Research)
Background: Low-density lipoproteins are oxidized and modified by macrophages. This process leads to the formation of macrophage-derived cholesterol-rich foam cells, which are a hallmark of early atherosclerosis. The accumulation of these form cells plays a crucial role in atherosclerosis progression. Allium hookeri (A. hookeri), a medicinal herb commonly used in Southeast Asia, is known for its various bioactive effects, including antioxidant, antibacterial, and antidiabetic properties. However, the repressive effect of A. hookeri extract on foam cell formation in THP-1 macrophages remains unclear. Objective: This study aims to explore the effect of A. hookeri hot water extract (AHWE) and its primary compound, cycloalliin, on foam cell formation. This investigation involves a combined treatment of oxidized low-density lipoprotein and lipopolysaccharide to stimulate the development of atherosclerosis in vitro. Additionally, the regulatory mechanisms underlying this process were elucidated. Design: THP-1 cells were differentiated by phorbol 12-myristate 13-acetate (PMA) (1 μM) for 48 h. Subsequently, they were treated with either AHWE or cycloalliin for 48 h. THP-1 macrophages were treated with combined ox-LDL (20 μg/mL) and LPS (500 ng/mL) for 24 h. Cell viability was assessed using MTT assays, while lipid accumulation was visualized through Oil Red O staining. The levels of corresponding proteins and mRNA were quantified using western blotting and quantitative polymerase chain reactions. Results: THP-1 cells were differentiated with PMA (1 μM) for 48 h and then treated with or without AHWE and cycloalliin for 48 h. Subsequently, THP-1 macrophages were treated with combined ox-LDL (20 μg/mL) and LPS (500 ng/mL) for 24 h before harvesting. Ox-LDL and LPS treatment for 24 h enhanced the lipid accumulation in foam cells compared to those in untreated cells using Oil red O staining. Conversely, AHWE and cycloalliin treatment inhibited lipid accumulation in foam cells. These treatments significantly upregulated cholesterol efflux-related genes, including ATP binding cassette subfamily A member 1 (ABCA1), liver-X-receptor ɑ (LXRɑ), and peroxisome proliferator-activated receptor gamma (PPARγ) expression. Additionally, AHWE and cycloalliin decreased lipid accumulation-related genes, including lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1), cluster of differentiation 36 (CD36), and scavenger receptor A1 (SR-A1) expression. Furthermore, the combined treatment of ox-LDL and LPS increased the activation and expression of nuclear factor-κB (NF-κB), cyclooxygenase-2 (COX-2), and pro-inflammatory cytokines (tumor necrosis factor-α [TNF-α] and IL-6) compared with those in untreated cells. However, AHWE and cycloalliin suppressed the expression of NF-κB, COX-2, TNF-α, and IL-6. Conclusions: AHWE and cycloalliin potentially play a crucial role in suppressing and protecting against early-stage foam cell formation by modulating lipid accumulation and cholesterol efflux. AHWE and cycloalliin have the potential to be effective agents for preventing atherosclerosis.